2021
DOI: 10.3390/life11040317
|View full text |Cite|
|
Sign up to set email alerts
|

Bromelain a Potential Bioactive Compound: A Comprehensive Overview from a Pharmacological Perspective

Abstract: Bromelain is an effective chemoresponsive proteolytic enzyme derived from pineapple stems. It contains several thiol endopeptidases and is extracted and purified via several methods. It is most commonly used as an anti-inflammatory agent, though scientists have also discovered its potential as an anticancer and antimicrobial agent. It has been reported as having positive effects on the respiratory, digestive, and circulatory systems, and potentially on the immune system. It is a natural remedy for easing arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
145
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 153 publications
1
145
0
2
Order By: Relevance
“…There is an urgent need to develop effective drugs and reasonable routes of intervertebral disc administration. Nanoparticles have large surface areas and pore volumes, which allow them to effectively load drugs [ 157 ]. A combination of a nanomaterial and oxymatrine increased drug anti-IDD activity, suggesting a novel route of drug administration [ 132 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…There is an urgent need to develop effective drugs and reasonable routes of intervertebral disc administration. Nanoparticles have large surface areas and pore volumes, which allow them to effectively load drugs [ 157 ]. A combination of a nanomaterial and oxymatrine increased drug anti-IDD activity, suggesting a novel route of drug administration [ 132 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Although soluble, Aβ40 is substantially more prevalent than soluble Aβ42; Aβ42 has a greater tendency for aggregation because of the hydrophobicity within its two terminal residues. In addition, Aβ42 is the key element of amyloid plaques, which has been found to be neurotoxic [ 66 , 73 , 74 ]. As a result, Aβ42 is assumed to be a critical participant in plaque development and AD pathogenesis [ 75 ].…”
Section: Pathogenesis Of Admentioning
confidence: 99%
“…Currently, it is known that the fight against many diseases involves proteolytic activity of bioactive peptides and various proteins, such as signaling molecules in inflammatory, allergic, and tumor processes, bacterial membrane proteins, and virus capsids [ 8 ]. The applications and herbal uses of bromelain (Bro) in various areas, such as food, medicine, and cosmetics, have been studied for decades [ 9 ] and important therapeutic applications have been reported for Bro in studies demonstrating its in vitro and in vivo anti-inflammatory, anti-coagulant, anti-tumor, anti-metastatic, and immunogenicity properties [ 10 ]. Clinical studies have also demonstrated Bro’s effectiveness in the treatment of burns (debridement), although many of these mechanisms have not yet been fully elucidated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%